The influence of soccer-specific fatigue on the risk of thigh injuries in amateur black African players - Jones, Robert Ian (Rhodes University, Faculty of Science, Department of Human Kinetics and Ergonomics, 2013)
Background: Epidemiological findings indicate a higher risk of muscular thigh strain injury during the latter stages of both halves of soccer match-play, with muscular fatigue highlighted as a key etiological factor in injury causation. Anthropometric, biomechanical and physiological differences present in the Black African population may elicit unique thigh injury risk profiles, different from those of European and American players. Objectives: The purpose of the current research was to investigate the impact of soccer-specific fatigue on the risk of hamstring and quadricep injury in amateur Black African soccer players, in both the dominant and non-dominant legs. Methods: Participants were required to perform a soccer matchplay simulation (SAFTâ ¹â °), consisting of multidirectional and utility movements, as well as frequent acceleration and deceleration. Selected physical, physiological and psychophysical responses were collected at specific time intervals throughout fatigue protocol performance. Results: Heart rate responses were observed to increase significantly (p<0.05) in response to the start of both halves, and remain elevated (but showing no further significant increase) during the performance of the remainder of the fatigue protocol. Significant (p<0.05) changes in both concentric and eccentric isokinetic variables of the knee flexors and extensors highlight the effect of muscular fatigue on performance in soccer match-play. Eccentric hamstring peak torque was observed to decrease significantly over time (60Â°.sâ »â‚‘=17.34%, 180Â°.sâ »â‚‘=18.27%), with significant reductions observed during both halves. The functional H:Q ratio at 180Â°.sâ »â‚‘ indicated a significant decrease over time (10.04%), with a significant decrease indicated during the second half of the SAFTâ ¹â ° protocol. The passive half time interval did not result in significant changes in isokinetic variables. Isokinetic strength, work and power indicated no significant effects of leg dominance.. 'Central' and 'Local' ratings of exertion were observed to increase significantly (p<0.05) as a function of exercise duration. Conclusion: The overall reduction in both the eccentric hamstring peak torque and the functional strength ratio was illustrated to be similar to that of other soccer-specific fatigue research. As a result, the risk of thigh strain injuries is suggested to be similar regardless of playing level and race. These time dependent changes may have implications for competitive performance and increased predisposition to hamstring strain injuries during the latter stages of both halves of match-play
Keywords: Soccer injuries -- South Africa -- Eastern Cape; Thigh -- Wounds and injuries -- South Africa -- Eastern Cape; Hamstring muscle -- Wounds and injuries -- South Africa -- Eastern Cape; Black people -- Wounds and injuries -- South Africa -- Eastern Cape; Fatigue